Legal Politics and Family Resilience from Ibn Khaldun's Perspective: A Study of the Muqaddimah and Its Relevance for Gaza Palestine - Muhamad Soleh; Nur Rohim Yunus; Imam Fachruddin (JURNAL ILMU SYARIAH, 2025)
The study of legal politics and family resilience is crucial for understanding the social dynamics of a nation, particularly when faced with a crisis. Ibn Khaldun, through his monumental work, al-Muqaddimah, provides an in-depth perspective on the relationship between the state, law, and family resilience within the context of human civilization. In general, his thinking emphasizes the importance of ʿasabiyyah (social solidarity) as the basis for political power and societal resilience. Specifically, this idea can be applied to understanding the contemporary situation in Gaza, where war, poverty, and social trauma have undermined family structures and weakened national resilience. This study aims to examine Ibn Khaldun's legal political thinking, particularly his views on the role of the family in supporting the continuity of the state, and to explore its relevance to the realities of families in Gaza. The method used is a qualitative research approach with a literature review approach, which explores Ibn Khaldun's classical literature and compares it with contemporary academic findings related to the Palestinian situation. The results indicate that the family plays a fundamental role as the last bastion in maintaining the existence of society, especially when the state fails to provide legal and political protection. The social solidarity initiated by Ibnu Khaldun was the key for the Palestinian people to survive colonialism, as well as the basis for building legal politics that sided with the people. Thus, Ibn Khaldun's thoughts are not only relevant in a historical context, but also provide a conceptual framework for solutions to Gaza's resilience today. Keywords: Legal Politics; Family Resilience; Ibn Khaldun; Al-Muqaddimah; Gaza Palestine